As contribui????es filos??fico-educacionais de Mario Osorio Marques - Lima, Andr?? Luiz Alves (2014)
The objective of this research was to investigate and systematize the thought of Mario Osorio Marques from his own work, highlighting and analyzing its theoretical foundations whose epistemology focused on the interaction between the actors of education in dialogue and reconstruction of knowledge as a form of deterrence of the educational process limited to the reproduction, storage and disposal, while at the same time as promoting the phenomenon of transformation and humanization of the historical subject. The delimitation of the research corpus was defined as: philosophical and educational thought marquesiano and their theoretical categories. And from that object was formulated the following problem: what were the theoretical categories in the work of Mario Osorio Marques and that they produced implication for education? The main hypothesis is that the categories engendered by Mario Osorio Marques were knowledge, pedagogy and learning involving training, especially humanizing of educators and students. The theoretical framework of this work lies in the design of Philosophy of Education for the significance of the educational phenomenon that led to Mario Osorio Marques an extensive academic output. In the case of a search-theoretical literature, the approach used was reading, documentation, analysis and interpretation of the major works of the author as primary sources, supplemented by grants and contributions from other theorists secondary sources whose contents available in books dissertations and doctoral theses, journal articles, and institutional sites that deal with the thought as well as on related topics and relevant to the object of study. These productions were used as quotes excerpts rationale for and development of the subject lectured. It is hoped that this research produce more elements to the appropriation of the philosophical-educational Mario Osorio Marques through a structured presentation of the same.